HEMODYNAMIC EFFECTS OF CARVEDILOL IN PATIENTS WITH ARTERIAL HYPERTENSION - L. I. Markova; A. I. Radzevich (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the influence of carvedilol (Talliton, Egis, Hungary) on daily profile of blood pressure (BP), anatomical and functional conditions of left ventricle (LV) and cerebral circulation in patients with arterial hypertension (AH), stage II-III. Material and methods. 30 patients (10 men, 20 women, average age 51,9±7,9 y.o.) with AH II-III stage ( RSSC,2004) and with initially affected daily profile of BP, cerebral circulation, anatomical and functional disorders of LV took carvedilol 25-75 mg/d during 6 months. Hemodynamics was estimated by ambulatory BP monitoring, Doppler Echocardiography, and ultrasound Dopplerography of extra cranial vessels. Results. A normalizing effect of carvedilol on abnormal daily profile of BP and cerebral circulation was determined. The treatment resulted in the regress of LV hypertrophy with predominant reduction of interventricular septum thickness and also the transformation of concentrical LV hypertrophy in excentrical one. Conclusion. Long-term therapy with carvedilol in patients with AH II-III stage provides a stable BP control and cardioprotective effect, improves cerebral circulation.